2022
DOI: 10.1007/s11695-022-05981-6
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of Telephone-Based Cognitive Behavioral Therapy on Mental Health Distress and Disordered Eating Among Bariatric Surgery Patients During COVID-19: Preliminary Results from a Multisite Randomized Controlled Trial

Abstract: Background Patients undergoing bariatric surgery have high rates of psychiatric comorbidity, which may increase their vulnerability to COVID-19-related mental health distress. Exacerbation of mental health distress and disordered eating could have significant negative effects on long-term weight management and quality of life for these patients if untreated. Objective To determine the efficacy of a telephone-based cognitive behavioral therapy (Tele-CBT) intervention in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Additionally, due to the short time frame in which the study will need to be conducted, the follow-up period for this study is limited to 3-month postintervention. Although previous research has shown that this short follow-up duration is sufficient in demonstrating the efficacy of the Tele-CBT intervention, 22 future studies could include additional follow-up timepoints to determine how the outcome measures change over prolonged periods of time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, due to the short time frame in which the study will need to be conducted, the follow-up period for this study is limited to 3-month postintervention. Although previous research has shown that this short follow-up duration is sufficient in demonstrating the efficacy of the Tele-CBT intervention, 22 future studies could include additional follow-up timepoints to determine how the outcome measures change over prolonged periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed effect sizes, SD and correlation between measurement pairs were estimated from the preliminary results in our current RCT. 22 While the trial is powered to detect differences in the multiple primary endpoints, a sample size of N=118 participants will achieve ≥90% power to detect differences in each of the secondary endpoints. Assuming an expected accrual rate of 11-12 participants per month across 4 sites, participant accrual is expected to complete in 12 months.…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…We offer a brief comparison of our findings to the literature to provide broader context, but we emphasize that this should be viewed cautiously given the paucity of treatment studies with patients following bariatric surgery (David et al, 2020;Sarwer & Heinberg, 2020;Stewart & Avenell, 2016), the dearth of interventions for LOC-eating, and the substantial differences across "broader relevant" studies in their methodologies, comparison groups, therapists, patient groups, and clinical settings. Initial reports for a low-intensity "CBT-type" telephone intervention also delivered 6 months postbariatric surgery indicated statistically significant short-term reductions among a mixed sample for binge-eating-related symptoms (not specifically LOC-eating), weight, and depression (Sockalingam et al, 2017(Sockalingam et al, , 2022. Reviews (David et al, 2020;Stewart & Avenell, 2016) of small trials (mainly brief low-intensity interventions without follow-ups) delivered postoperatively (without assessment of LOC-eating or binge eating) have reported some instances of statistically significant acute weight losses but the main findings tend to be modest and mixed.…”
Section: Discussionmentioning
confidence: 99%